RESPON MASYARAKAT TERHADAP METODE PNPM P2KP : PENGALAMAN MASYARAKAT SADANG SERANG KOTA BANDUNG - Indrianingrum, Lulut (Jurnal Teknik Sipil dan Perencanaan, 2011)
Abstract: PNPM P2KPÃÂ  (national program of community empowerment Ã¢â¬â urban poverty alleviation program) has been changing the communityÃ¢â¬â¢s habit in managing the neighbourhood. The method is new, covering manyÃÂ  locations ofÃÂ  implementation-as national program,ÃÂ  limitedÃÂ  time of socialization and demanding a real output in short period. These backgroundsÃÂ  leadÃÂ  to a critical question of how doesÃÂ  the communityÃÂ  responseÃÂ  to manage PNPM P2KP withinÃÂ  theÃÂ  traditional way of managingÃÂ  the neighbourhood?. This paper aimsÃÂ  to describeÃÂ  the communityÃ¢â¬â¢sÃÂ  responseÃÂ  to participatory planning (asÃÂ  the spirit of PNPM P2KP) whenÃÂ  they areÃÂ  implementingÃÂ  the programÃ¢â¬â¢s method. TheÃÂ  location of studyÃÂ  is ÃÂ inÃÂ  SadangÃÂ  SerangÃÂ  SubÃÂ  DistrictÃÂ  inÃÂ  BandungÃÂ  Municipality.ÃÂ  SadangÃÂ  SerangÃÂ  hasÃÂ  been participatingÃÂ  inÃÂ  thisÃÂ  programÃÂ  sinceÃÂ  2004.ÃÂ  DuringÃÂ  theÃÂ  projectÃÂ  period,ÃÂ  theÃÂ  communityÃÂ  foundÃÂ  a complicated way ofÃÂ  implementingÃÂ  the programÃ¢â¬â¢s method. They have not been acquainted withÃÂ  the participatory method butÃÂ  the program did not giveÃÂ  them enoughÃÂ  timeÃÂ  to understandÃÂ  the rogramÃ¢â¬â¢s objective.ÃÂ  InÃÂ  the other words, The programÃÂ  that should be participatory-based wasÃÂ  implementedÃÂ  in project-based. ÃÂ TimeÃÂ  isÃÂ  theÃÂ  keywordÃÂ  ofÃÂ  thisÃÂ  matterÃÂ  becauseÃÂ  participatoryÃÂ  methodÃÂ  willÃÂ  giveÃÂ  the community unlimited time to interact with the program. CommunityÃ¢â¬â¢s responses were collected from interviews withÃÂ  the communityÃ¢â¬â¢s boardÃÂ  (BKM) asÃÂ  theÃÂ  local comitee of PNPM P2KP and community member in Sadang Serang. ÃÂ  Keywords: CommunityÃ¢â¬â¢s response, PNPM P2KP Method ÃÂ  Abstrak:ÃÂ  PNPMÃÂ  P2KPÃÂ  (ProgramÃÂ  PenanggulanganÃÂ  KemiskinanÃÂ  Perkotaan)ÃÂ  yangÃÂ  dilaksanakanÃÂ  di IndonesiaÃÂ  telahÃÂ  banyakÃÂ  mengubahÃÂ  kebiasaan-kebiasaanÃÂ  masyarakatÃÂ  dalamÃÂ  mengelola lingkungannya.ÃÂ  MetodeÃÂ  yangÃÂ  diterapkanÃÂ  dalamÃÂ  P2KPÃÂ  dianggapÃÂ  baruÃÂ  olehÃÂ  masyarakatÃÂ  yangÃÂ  meliputi banyak lokasi pelaksanaan sebagai program nasional, waktu sosialisasi yang terbatas dan menuntutÃÂ  keluaranÃÂ  yangÃÂ  nyataÃÂ  padaÃÂ  periodeÃÂ  yangÃÂ  singkatÃÂ  (padaÃÂ  programÃÂ  partisipasi).ÃÂ  Hal-hal tersebutÃÂ  merupakanÃÂ  faktaÃÂ  yangÃÂ  melatarbelakangiÃÂ  pertanyaanÃÂ  kritisÃÂ  bahwaÃÂ  bagaimanaÃÂ  respon masyarakat dalam mengelola program PNPM P2KP ditengahÃÂ  cara-caraÃÂ  konvensionalÃÂ  yang biasa dilakukan masyarakat dalam mengelolaÃÂ  lingkungannya. ArtikelÃÂ  ini bertujuan untuk mendiskripsikan respon masyarakatÃÂ  pada metodeÃÂ  perencanaanÃÂ  partisipatifÃÂ  (sebagaiÃÂ  intiÃÂ  dariÃÂ  PNPMÃÂ  P2KP)ÃÂ  ketika program ini dijalankan. Lokasi studi terletak di Kelurahan Sadang Serang Kota Bandung. Kelurahan ini telah melaksanakan program P2KP sejak 2004. Selama periode program, masyarakat menemui kesulitan dalam menjalankan metode program yang diterapkan. Masyarakat belum terbiasa dengan metode P2KP namun waktu yang diberikan pada masyarakat belum cukup untuk memahami tujuan program.ÃÂ  DenganÃÂ  kataÃÂ  lain,ÃÂ  programÃÂ  yangÃÂ  seharusnyaÃÂ  dilaksanakanÃÂ  denganÃÂ  dasarÃÂ  partisipatif, dilaksanakan dengan dasar proyek. Waktu merupakan kunci dari permasalahanÃÂ  ini karena metoe partisipatif akan memberikan waktu yang tidak terbatas bagi masyarakat untuk berinteraksi dengan program.ÃÂ  Respon-responÃÂ  dariÃÂ  masyarakatÃÂ  dianalisaÃÂ  dariÃÂ  wawancaraÃÂ  denganÃÂ  BKMÃÂ  (Badan Keswadayaan Masyarakat) sebagai pegelola P2KP dan anggota masyarakat di Sadang Serang. ÃÂ  Kata kunci : respon masyarakat, metode PNPM P2KP